Effect of limited enzymatic hydrolysis on the structure and emulsifying properties of rice bran protein. (January 2019) - Zang, Xiaodan; Yue, Chonghui; Wang, Yuxin; Shao, Meili; Yu, Guoping
Abstract: The influence of the degree of hydrolysis (DH) on the structure, solubility and emulsifying properties of rice bran protein (RBP) was investigated. Sodium dodecyl sulfide polyacrylamide gel electrophoresis (SDS-PAGE), intrinsic fluorescence, surface hydrophobicity and circular dichroism (CD) techniques were used for the analysis of the structural characteristics. Hydrolysis can change the molecular weight of the protein, increase its flexibility and fluidity, change its surface hydrophobicity, and increase its solubility. Oil-in-water emulsions were prepared from rice bran protein hydrolysates (RBPH) with different DH values (1%, 3%, and 6%). The stabilities of the RBPH-stabilized emulsions were investigated under the following environmental pressures: pH (3–9), ionic strength (0–300 mM NaCl) and thermal treatment (30–90 °C, 30 min). Particle size and surface charge (ζ-potential) were measured as an indication of the emulsion stability. Emulsions prepared with 3% DH RBP were much more stable than the emulsions prepared with RBPH with other DH values, and this RBP has potential as an emulsifier in the food industry. Highlights: Limited hydrolysis of rice bran protein to enhance its emulsification. The structure of proteins and hydrolysates were investigated. Emulsions prepared with 3% DH rice bran protein were more stable.